2003
DOI: 10.1515/jbcpp.2003.14.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Captopril and Enalapril Improve Cognition and Depressed Mood in Hypertensive Patients

Abstract: Untreated hypertensive patients scored lower than normotensive controls in cognitive tests and significantly worse in cumulative recall (P < 0.05) and paired words association (P < 0.01). When compared with normotensive subjects, untreated hypertensive patients also scored significantly higher on the depression with anxiety subscale in HSC (P < 0.05). No significant influence of hypertension was found in any other examined aspect of cognition and mood. In most cases captopril improved and enalapril reversed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 55 publications
2
52
0
3
Order By: Relevance
“…Among the affective disorders, the depression can coexist with the development of cardiocirculatory disturbances (Braszko et al 2003). In this condition it is frequent the diagnosis of 5-HTergic hypofunction performed through the proof of the capacity of prolactin release after administration of 5-HT releaser (Meltzer and Lowy 1987).…”
Section: Hypertensionmentioning
confidence: 99%
“…Among the affective disorders, the depression can coexist with the development of cardiocirculatory disturbances (Braszko et al 2003). In this condition it is frequent the diagnosis of 5-HTergic hypofunction performed through the proof of the capacity of prolactin release after administration of 5-HT releaser (Meltzer and Lowy 1987).…”
Section: Hypertensionmentioning
confidence: 99%
“…In this way, captopril was reported by many authors to have a beneficial effect on cognition, attention and emotional functions (5)(6)(7)16). Also, it was reported that icv administration of Ang II results in increased anxiety-like behavior in rats (17).…”
Section: Discussionmentioning
confidence: 90%
“…Also, it was reported that icv administration of Ang II results in increased anxiety-like behavior in rats (17). In addition, captopril has been suggested to possess antidepressant activity, as shown by specific tests like forced-swimming and learned helplessness (6,18). Still, there are studies which failed to find any effects of captopril on cognition, subjective feeling or mood (8) in human patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study reported a greater incidence of depressed mood associated with anxiety and decreased cognitive function in patients with hypertension. These deficits were absent in hypertensives taking ACE inhibitors (Braszko, Karwowska-Polecka, Halicka, & Gard, 2003). Interestingly, patients taking ACE inhibitors or angiotensin II receptor antagonists are more likely to continue drug therapy compared to patients taking other antihypertensive medications (Elliott, Plauschinat, Skrepnek, & Gause, 2007).…”
Section: Definitionmentioning
confidence: 98%